Global Performance Evaluation - Soetjipto, Budi W. (Forum Manajemen, 1997)
Prformance evaluation is defined as an ongoing process of evaluating and managing both the behavior and outcomes in the work place (Carrell, Elbert and Hatfield, 1995). Performance evaluation is both a system of papers and procedures designed by the organization foruse by its managers (the evaluation system), and an interpersonal process in which manager and subordinate communicate and attempt to influence each other (the evaluation process or interview) (Beer, 1977).